MODEL DISTRIBUSI SPASIAL HABITAT ELANG JAWA (Nisaetus bartelsi) YANG TERSISA DI JAWA BARAT - Azmi, Nur; ., Syartinilia; Mulyani, Yeni A. (Media Konservasi, 2016)
Javan Hawk-Eagle (JHE, Nisaetus bartelsi) which is endemic raptor in the natural forests of Java, Indonesia is categorized as one of the endangered. Small population size, severe habitat loss, forest fragmentation, and illegal hunting have contributed to the ‘‘endangered’’ status of this species. Moreover, conservation of this species has become a national priority. This study was being conducted because of the lack of information about the distribution of JHE’s remnants habitat which caused the proposed conservation strategies for JHE become difficult. This study aimed for updating data of JHE’s remnants habitat in West Java, analyzed its habitat patches distribution, and estimated the number of its populations. The previous study determined the habitat suitability probability modelling of JHE with used landsat images in 2002 at southern part of West Java. This study updated the model using the same logistic regression model equation in West Java overall. This study identified 17 remnant habitat patches (3 955 km2) scattered in West Java. The comparison with previous study showed that the size and number of patches was increased with the predicted number of JHE’s populations were about 39-195 (median = 117) pairs in southern part of West Java. Based on the results, we offer three recommendations to increase the survival of JHE’s habitat in West Java. Keywords: GIS, habitat remnants, logistic regression, Nisaetus bartelsi, patch.